A Cross-Sectional Study on Bullying and Psychological Disturbances among Malaysian School Children - Md Isa, Muhammad Lokman; Mocktar, Nurfatin Aina; Ibrahim, Wisam Nabeel; Nurumal, Mohd Said; Che Hasan, Muhammad Kamil (UI Scholars Hub, 2021)
Background: Bullying is a common violence in school and has become a major public health and global concern. Bullying influences mental health and is identified as a leading factor of depression. Therefore, this study aimed to identify bullying prevalence and its association toward psychological disturbances (stress, anxiety, and depression). Methods: This cross-sectional study was conducted in three secondary schools in Kuantan. After obtaining consent from parents/guardians, participants were asked to answer a self-administered questionnaire, including School Climate Bullying Survey, Depression Anxiety Stress Questionnaire-21, Patient Depression Questionnaire, and Generalized Anxiety Disorder. Demographic data were self-reported. Data were analyzed using SPSS version 20.0, and chi-square and correlation tests were conducted for variables. Results: A total of 207 students were included in this study. Of respondents, 50.7% were boys and 49.3% girls, and the majority (92.8%) were Malays. Of students, 63.2% were involved in bullying problems through the school years, with verbal bullying as the highest (55.1%). Bullying is significantly associated with stress (p = 0.045), anxiety (p = 0.018), and depression (p = 0.012). Conclusions: School children in Kuantan continue to be involved in bullying. The current study supported that involvement with any bullying activity was associated with psychological disturbances including anxiety, stress, and depression.